Kajian Strategi Penerapan Pembangunan Berkelanjutan - Wiryananda, Ngakan Gede Agung Khrisna; I Gede Andy Andika , Parahita (Jurnal Lingkungan Almuslim, 2022)
Sustainable development requires three aspects that must be balanced, namely economic, socio-cultural, and environmental. The implementation of sustainable development that has been carried out has not shown maximum results. The purpose of this research is to formulate a strategy to implement sustainable development derived from practices that have been carried out in various countries. This research uses literature study method with descriptive analysis. The results of this study are to obtain six strategies that can be used to achieve sustainable development. The six strategies are the fulfillment of social and security rights, community participation and utilization of local wisdom, provision of infrastructure, utilization of technology, information, and communication, strong political and legal commitment, and collaboration of various parties.